Simulation analysis of micro coils for the fabrication of micro-scaled search coil magnetometer - Tengku Azmi, Tengku Muhammad Afif; Sulaiman, Nadzril (IEEE, 2016)
Magnetic field detection has been widely accepted in many applications such as military systems, outer space exploration and even in medical diagnosis and treatment. Low magnetic field detection is particularly important in tracking of magnetic markers in digestive tracks or blood vessels. The presence of magnetic fields’ strength and direction can be detected by a device known as magnetometer. A magnetometer that is durable, room temperature operation and having nonmovable components is chooses for this project. Traditional magnetometer tends to be bulky that hinders its inclusion into micro-scaled environment. This concern has brought the magnetometer into the trend of device miniaturization. Miniaturized magnetometer are usually fabricated using conventional microfabrication method particularly surface micromachining in which micro structures are built level by level starting from the surface of substrates upwards until completion of final structure. Besides time consuming, this method requires many consecutive steps in fabrication process and careful alignment of patterns on every layer which increase the complexity. The issue of miniaturization and complexity of conventional fabrication process has lead to this investigative research. The main objective of this research is to investigate and analyze the best and reliable micro coil for search coil magnetometer. Simulations and analysis for microscaled coil that is capable of detecting low magnetic field are done. The expected work include investigation on possible magnetometer of detecting low magnetic field, designing micro scale magnetometer, complete device fabrication processes, testing and characterization of the fabricated prototype device. Based on the results of simulation, a search coil magnetometer of 60m thickness with spacing of 60m and 30 turns was designed.